1976
DOI: 10.1259/0007-1285-49-577-12
|View full text |Cite
|
Sign up to set email alerts
|

The detection and significance of calcifications in the breast: a radiological and pathological study

Abstract: The radiological detection of calcification is compared using xeroradiography, non-screen film and a film-screen combination. The "threshold" values of the smallest detectable size of calcification, under simulated clinical conditions, are found to be approximately 100 mum for xeroradiography and 400 mum for both the film techniques in this study. The incidence of calcification seen on the preoperative mammograms of patients with carcinoma of the breast is 48-5 per cent. Further calcification revealed by histo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0
1

Year Published

1977
1977
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(29 citation statements)
references
References 15 publications
1
27
0
1
Order By: Relevance
“…The increased risk associated with this genetic variant in postmenopausal women is consistent with the knowledge that estrogens are regulators of calcium influx (29) and that postmenopausal women absorb calcium less efficiently (30,31). It has been postulated that microcalcification is a result of abnormal calcium deposition and mineralization of necrotic debris (32,33). We found that the RYR3 G allele (GG + GA) genotypes were significantly associated with microcalcification in breast cancer tissues.…”
Section: Discussionsupporting
confidence: 87%
“…The increased risk associated with this genetic variant in postmenopausal women is consistent with the knowledge that estrogens are regulators of calcium influx (29) and that postmenopausal women absorb calcium less efficiently (30,31). It has been postulated that microcalcification is a result of abnormal calcium deposition and mineralization of necrotic debris (32,33). We found that the RYR3 G allele (GG + GA) genotypes were significantly associated with microcalcification in breast cancer tissues.…”
Section: Discussionsupporting
confidence: 87%
“…Breast cancer is one of the malignant neoplasms that can [2][3][4][5][6]. This phenomenon is not limited to lobular carcinoma in situ, where it has been well accepted that the calcium is often next to but not within the actual carcinoma [9,10].…”
Section: Discussionmentioning
confidence: 99%
“…Although the origin of calcifications in mammary carcinomas is unclear, the suggested mineralization of cellular debris and degenerative tumor cells (19) could indicate a high tumor growth rate. The presence of microcalcifications is often the first recognizable mammographic sign of a developing malignancy.…”
Section: Discussionmentioning
confidence: 99%